Study of Dysgeusia and Anosmia Frequency and Risk Factors in Pre-Elderly Post-Covid-19 - Ari Tri Wanodyo Handayani; Zahreni Hamzah; Dwi Prijatmoko; Dyah Indartin Setyowati; Hosea Ferdinan (Jurnal Kedokteran Brawijaya, 2023)
Covid-19 is a respiratory obstruction caused by infection with SARS-CoV-2. The appearance of dysgeusia and anosmia can be a sign that someone has contracted this virus. This study aims to review the frequency and risk factors that cause dysgeusia and anosmia in pre-elderly post-Covid-19. This type of research is descriptive observational with a cross-sectional approach. In this study, only 5.15% of respondents experienced anosmia, 10.31% of dysgeusia alone, and 28.86% of dysgeusia accompanied by anosmia. Dysgeusia and anosmia can be found in every vaccination status. Respondents with ≥1 dominant comorbid were found in respondents who experienced dysgeusia accompanied by anosmia. Symptoms of fever, cough, rhinorrhea, and pneumonia are common in dysgeusia and anosmia disorders. The time of appearance of the disturbance ranges from 1-7 days, with the duration of the disruption 1-14 days. Symptoms of dysgeusia accompanied by anosmia in the pre-elderly post-Covid-19show a higher frequency than dysgeusia alone and anosmia alone. In pre-elderly, men were found to be more at risk than women. Several risk factors, including the aging process, co-morbidities, smoking habits, and vaccination status, support the emergence of these symptoms.